Penggunaan Media Sosial dalam Penyebarluasan Informasi Program Pemerintah di Dinas Komunikasi Informatika Statistik dan Persandian Kabupaten Rokan Hilir Provinsi Riau - Lisdawati, Yuni (Jurnal Teknologi dan Komunikasi Pemerintahan, 2022)
Abstract The author focuses on several problems related to the use of social media in disseminating information on government programs in Rokan Hilir Regency Riau Province such as the lack of use of social media by local officials, limited social media manager and the provision of information that is not evenly distributed to the public. This study aims to know the use of social media in the dissemination of government program information in the Department Of Statistical Information Communication And Cryptography Rokan Hilir regency of Riau Province. This study uses qualitative research design descriptive methods and inductive approaches with analysis of the uses and gratifications theory by Lometti, Reeves, Bybee and the theory of open government by OECD (Organization for Economic Co-operation and Development). The technique of collecting data are done by observation, interviews and documentation. The findings are the use of social media in the dissemination of government program information has not been said well based on the dimensions of the amount of time social media use is still relatively lacking, the dimensions of media content, transparency and accountability are low despite the dimensions of media relations with individuals public involvement in the fairly good category. The use of social media in disseminating information on government programs at the Office of Communication, Informatics, Statistics and Cryptography, Rokan Hilir Regency, Riau Province is still not good, this is due to lack of apparatus resources, lack of providing information to the public about official social media and limited service infrastructure. In order to increase the use of social media in disseminating information, it is recommended to improve the quality and quantity of the apparatus, improve infrastructure and collaborate with other parties. Keywords: Information, Media, Government Abstrak Penulis berfokus pada beberapa permasalahan berkaitan dengan penggunaan media sosial dalam penyebarluasan informasi program pemerintah di Kabupaten Rokan Hilir Provinsi Riau yaitu kurangnya penggunaan media sosial oleh perangkat daerah, pengelola media sosial yang terbatas serta pemberian informasi yang tidak merata kepada masyarakat. Tujuan dari penelitian ini adalah untuk mengetahui penggunaan media sosial dalam penyebarluasan informasi program pemerintah di Dinas Komunikasi Informatika Statistik dan Persandian Kabupaten Rokan Hilir Provinsi Riau. Penelitian ini menggunakan desain penelitian kualitatif metode deskriptif dan pendekatan induktif dan analisis terhadap teori kegunaan dan kepuasan oleh Lometti, Reeves, Bybee serta teori pemerintahan terbuka dari OECD (Organization for Economic Co-operation and Development). Teknik pengumpulan data dilakukan dengan observasi, wawancara dan dokumentasi. Temuan yang diperoleh penulis dalam penelitian ini yaitu penggunaan media sosial dalam penyebarluasan informasi program pemerintah harus dioptimalkan, berdasarkan dimensi jumlah waktu penggunaan media sosial masih tergolong kurang, dimensi isi media, transparansi dan akuntabilitas termasuk rendah meskipun dimensi hubungan media dengan individu keterlibatan publik dalam kategori cukup baik. Penggunaan media sosial dalam penyebarluasan informasi program pemerintah di Dinas Komunikasi Informatika Statistik dan Persandian Kabupaten Rokan Hilir Provinsi Riau masih perlu pengoptimalan, hal ini dikarenakan adanya sumber daya aparatur yang kurang, kurangnya pemberian informasi kepada masyarakat mengenai media sosial yang resmi serta keterbatasan sarana prasarana dinas. Guna meningkatkan penggunaan media sosial dalam penyebarluasan informasi, disarankan untuk melakukan peningkatan kualitas dan kuantitas aparatur, peningkatan sarana prasarana serta melakukan kerjasama dengan pihak lain. Kata kunci: Informasi, Media, Pemerintah